BASIS FOR DESIGN OF THE FUNCTIONAL MODEL OF RESEARCH TRAINING OF TECHNICAL UNIVERSITY STUDENTS - Gorshkova, Оksana (Revista Inclusiones, 2020)
The relevance of the problem under study is conditioned by the current discrepancy between the society demand for competent engineering staff prepared for research activities and poor development of the theoretical and methodical basis of students’ research training. Peculiarities of engineering activities, integration of a competence approach into engineering education, adoption of educational and occupational standards result in a brand new approach to students’ training and bring about a need for a teaching model targeted at preparing graduates for research activities. The aim of the article is to settle the problem of developing and implementing the functional model of students’ research training in the context of competence-oriented engineering education that would define the content of innovative didactics and allow to reach the goals set in engineering education. This paper arranges, singles out, and develops current approaches to solving the problem of research training of technical university students that contribute to the development of a methodological framework of this preparation as a functional model. Empiric methods (polling, observation, interviews, testing, selfassessment, document review, study of deliverables, educational design) enabled analysis of the maturity level of research competence of first-year students and graduates before the start of the experiment, after each stage of the experiment and at the end of the experiment. 1,520 persons were engaged, including 1,390 students and 130 teachers. The educational experiment was targeted at evaluating functional model performance by identifying changes in the maturity level of the students’ research competence.